PROTECTIVE EFFECT OF γ-AMINOBUTYRIC ACID ON ANTIOXIDATION FUNCTION IN INTESTINAL MUCOSA OF WENCHANG CHICKEN INDUCED BY HEAT STRESS - Z. Chen; J. Tang; Y. Q. Sun; J. Xie (Journal of Animal and Plant Sciences, 2013)
This study was conducted to explore the effects of heat stress (HS) and γ-aminobutyric acid (GABA) on antioxidation in intestinal mucosa of Wenchang chickens. One-day-old male chickens were randomly divided into GABA and control (CK) groups after 15 days feeding. The chicken from GABA group fed with 0.2 ml GABA solution and the chicken from CK group fed with 0.2 ml normal saline daily. At the age of 35 days, chickens in two groups were then divided into normal group (HSB), heat stress group (HSA) and heat stress recovery group (HSR), respectively. HSA and HSR were conducted in an environment of 40 ± 0.5 °C for 3 h. Results indicated that the activities of antioxidase and T-AOC in HSA group were lower than those in HSB and HSR groups; the content of MDA was higher than that in HSB and HSR groups. On the other hand, the activities of antioxidase and T-AOC in GABA group was higher than those in CK group and the content of MDA from GABA group was lower than that from CK group. In a word, heat stress caused a significant antioxidative damage to chicken small intestinal mucosa. In contrast, GABA can effectively alleviate the damage.
Keywords: GABA; heat stress; intestinal mucosa; antioxidation function; chicken